Interdisciplinary approach to clinical placements within Charles Sturt University School of nursing Midwifery and Indigenous Health : a practice report - Biles, Jessica Maree; Biles, Brett James; McMillan, Faye (Student success, 2015)
The clinical placement environment can be challenging for many students, and for students enrolled in the Charles Sturt University School of Nursing, Midwifery and Indigenous Health (SNMIH) subject NRS194, Indigenous Cultures, Health and Nursing, being placed in an Aboriginal facility can be daunting and increase anxiety within a cohort. A pilot project within the SNMIH for NRS194 sought to engage the local Aboriginal Health Service through Aboriginal staff and utilising the skills, knowledge and expertise of the Aboriginal Health workers as a conduit to the community. The cross cultural engagement within the SNMIH and the community has meant the cohorts of discipline-specific programs are being exposed to a breadth and depth of diversity within the Australian Health context, with a specific focus on Aboriginal and Torres Strait Islander peoples and their communities. This practice report discusses the core elements of this first year placement initiative and the outcomes from the academic lens. [Author abstract, ed]